P846 Genetics, methylation, and disease state interact at the VMP1/MIR21 locus. (16th January 2018) - O'Leary, K; Adams, A; Nimmo, E; Ventham, N; Satsangi, J
Abstract: Background: Altered methylation at the VMP1/MIR21 locus in association with IBD has been demonstrated several times (Adams et al ., 2014; Ventham et al ., 2016), with the latter finding significant correlations (meQTLs) between methylation at this locus and the genetic variants rs10853015 and rs8078424. These are in linkage disequilibrium with the known IBD-associated variant rs1292053 (Jostins et al ., 2012), located 47 kb downstream. This region is of potential importance in IBD pathogenesis as the methylation changes are in the promoter region of inflammation-associated microRNA mir21, which is found in the core autophagy gene VMP1. The aim of this study was to confirm the VMP1/MIR21 meQTL in an independent cohort and examine the mir21 primary sequence (pri-mir21) for novel SNPs. Methods: 300 patients were chosen from a large cohort collected at the Western General Hospital, Edinburgh comprising 100 healthy controls (HC), 100 ulcerative colitis patients (UC) and 100 Crohn's disease patients (CD). Sanger sequencing of a 6.5kb region around the miR21 locus was processed and aligned using R and SMALT (Genome Research Ltd.). Known SNPs from european populations in dbSNP (v150) were checked and the sequence was examined for new SNPs. Methylation at the VMP1/MIR21 locus was measured by a previously described pyrosequencing assay (Adams et al ., 2014). MeQTL analysis was performed in R, using the Sanger sequencing results, and previously generated Immunochip genotyping data. Results: Analysis of the Immunochip data and pyrosequencing data confirms the correlation between VMP1/MIR21 methylation and the genotypes of GWAS SNP rs1292053 and four surrounding SNPs. Low minor allele frequencies of the known SNPs within pri-mir21 precluded the finding of significant meQTLs although non-significant trends were observed. No novel SNPs within the pri-mir21 sequence were identified in this cohort. Conclusions: Pri-mir21 is known to be highly conserved and no novel SNPs were found in this cohort. There is further evidence that the well-established disease-associated methylation change is correlated with underlying genetic differences, including SNPs which have been shown to increase risk for IBD in large well-powered GWAS meta-analyses. The importance of mir21 in numerous inflammatory processes, and its host gene VMP1's critical role in autophagy strengthen the argument for further functional work on these targets.